Pengaruh Economic Value Added dan Market Value Added terhadap Tobin’s Q dan Dampaknya terhadap Harga Saham pada Subsektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017 – 2021 - Pantun Bukit; R. Adisetiawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research aims to determine the influence of Economic Value Added and Market Value Added on Tobin’s Q and the impact on Stock Price in the Food and Beverages Industry. There are 10 companies that will be used as sample in this study, that selected using the purposive sampling method. This research uses secondary data and to collect the data by using library research. This research is a descriptive quantitative research and uses an analytical tool, namely path analysis. The first path analysis stucture shows that the direct effect of Economic Value Added (X1) and Market Value Added (X2) on Tobin’s Q (Y) is 43,19%, indirect effects descreased by 12,52%, so the total effect is 30,67%. The second path analysis stucture shows that the direct effect of Economic Value Added (X1) and Market Value Added (X2) on Stock Price (Z) is 42,89%, indirect effects descreased by 14,04%, so the total effect is 28,85%. The third path analysis stucture shows that the effect of Tobin’s Q (Y) on Stock Price (Z) is 62,88%. The fourth path analysis stucture shows that the total effect of Economic Value Added (X1) and Market Value Added (X2) on Stock Price (Z) through the Tobin’s Q (Y) is 15,01%, and the research beyond the variabel is 84,99%, which is the contribution of other variables beyond the existing research variables.